2016
DOI: 10.1007/s10111-016-0373-3
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty management in enroute air traffic control: a field study exploring controller strategies and requirements for automation

Abstract: The management of uncertainty is a critical aspect of current as well as future air traffic control operations. This study investigated: (1) sources of uncertainty in enroute air traffic control, (2) strategies that air traffic controllers adopt to cope with uncertainty, (3) the tradeoffs and contingencies that influences the adoption of these uncertainties, and (4) the requirements for system design that support controllers in following these strategies. The data were collected using a field study in two enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 49 publications
0
12
0
1
Order By: Relevance
“…Some factors are interchangeable (mutual performance monitoring and team leadership), but these still affect the other factors, their relative importances, and how they are manifested. Corver and Grote (2016) showed that ATCOs prefer to do what is "common sense" or "what is safe" in situations where they do not know the established procedures, and in situations in which established procedures are not applicable. This agrees with the findings of the present study, where the ATCOs emphasise that shared mental models are important.…”
Section: Overall Discussionmentioning
confidence: 99%
“…Some factors are interchangeable (mutual performance monitoring and team leadership), but these still affect the other factors, their relative importances, and how they are manifested. Corver and Grote (2016) showed that ATCOs prefer to do what is "common sense" or "what is safe" in situations where they do not know the established procedures, and in situations in which established procedures are not applicable. This agrees with the findings of the present study, where the ATCOs emphasise that shared mental models are important.…”
Section: Overall Discussionmentioning
confidence: 99%
“…In both cases, the ATCO will not trust the tool and abandon its use. Corver and Grote (2016) proposed a field study exploring the sources of uncertainties and the different management strategies adopted by controllers. Building tools to help controllers in their detection and resolution task has been source of experimental research since the early 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty management plays a key role in air traffic control. Corver and Grote (2016) recently proposed a field study exploring sources of uncertainties and management strategies adopted by controllers. Some of the first research experiments on controller assistance tools were carried out in the 1990s.…”
Section: Introductionmentioning
confidence: 99%